Evaluasi Efektivitas Intervensi pada Ibu Hamil dengan Anemia di Indonesia: Studi Literatur - Tri Riwayati Ningsih; Fitri Windari; Heni Anggraini; Dwi Rosmawati (SEHATI: Jurnal Kesehatan, 2024)
An in-depth understanding of the background of the problem of anemia in pregnant women in Indonesia is crucial for designing and implementing more effective intervention programs. Effective prevention and intervention programs and efforts to holistically increase nutritional awareness in society are a must to achieve positive change in overcoming anemia in pregnant women in Indonesia. To analyze more deeply the extent to which previous research has investigated interventions for pregnant women with anemia in Indonesia. This research uses the PRISMA literature review, through a digital library database that is connected to various scientific publication pages through keywords such as "Anemia", "Pregnant Women", "Anemia of Pregnant Women", and "Anemia Intervention". Research methods include quantitative, qualitative methods and reviews related to intervention strategies for pregnant women with anemia in Indonesia. Effective interventions for pregnant women with anemia include health education, a combination of blood supplement tablets and juices and consumption of iron from natural sources. Interventions based on a sustainable and integrated approach, involving various parties including families, communities, government, private parties and non-government partners, are needed to achieve significant and sustainable changes in tackling anemia in pregnant women in Indonesia.